Respuesta :

Notice that

[tex](2x^3-xy^2-2y+3)_y=-2xy-2[/tex]

[tex](-x^2y-2x)_x=-2xy-2[/tex]

so the ODE is exact, and we can find a solution [tex]F(x,y)=C[/tex] such that

[tex]F_x=2x^3-xy^2-2y+3[/tex]

[tex]F_y=-x^2y-2x[/tex]

Integrating both sides of the first equation wrt [tex]x[/tex] gives

[tex]F(x,y)=\dfrac{x^4}2-\dfrac{x^2y^2}2-2xy+3x+g(y)[/tex]

Differentiating wrt [tex]y[/tex] gives

[tex]F_y=-x^2y-2x=-x^2y-2x+g'(y)\implies g'(y)=0\implies g(y)=C[/tex]

So we have

[tex]\boxed{F(x,y)=\dfrac{x^4}2-\dfrac{x^2y^2}2-2xy+3x=C}[/tex]